Monatomic alloy photocatalyst as well as preparation method and application thereof
By using the synergistic action of Cu and Au in the photocatalyst, doping Au atoms onto Cu nanoparticles, a single-atom alloy photocatalyst is prepared, which solves the problem of low efficiency and selectivity of photocatalytic carbon dioxide conversion to ethanol, and achieves efficient and low-cost ethanol conversion, with industrial application potential.
Patent Information
- Application Number
- CN202510187917.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The efficiency and selectivity of photocatalytic conversion of carbon dioxide into C2+ products such as ethanol is not high, especially the selectivity of ethanol.
Through the synergistic effect between Cu and Au, wet mixing and atomic replacement reduction method are used to dopate metal Au atoms on the Cu nanoparticles on the surface of the support, and a single-atom alloy photocatalyst is prepared to adjust the surface charge of the catalyst to improve the *CO adsorption capacity and reduce the reaction energy barrier of carbon-carbon coupling.
The efficient and selective conversion of photocatalytic carbon dioxide into ethanol is achieved, and the efficient ethanol conversion rate can be achieved under pure water conditions, reducing the cost of raw materials, and conducive to the industrial promotion of catalysts.
Smart Images

Figure CN119657171A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon dioxide recycling, and in particular to a single-atom alloy photocatalyst and a preparation method and application thereof. Background Art
[0002] Solar-driven reduction of CO2 to green, clean fuels is widely considered a key way to alleviate the energy crisis and climate warming. Photocatalytic CO2 reduction has made significant progress in producing C1 products (CO, CH4, methanol, etc.). However, the selective conversion of CO2 to C2 and above products (such as ethanol and acetic acid) still faces major challenges, because the photocatalytic conversion of CO2 to C2 products involves complex multi-electron transfer and CC coupling processes, in which extremely high reaction energy barriers and slow kinetic processes limit multi-carbon. To overcome these challenges, photocatalysts are crucial.
[0003] Plasmonic metal nanoparticles are ideal materials for enhancing photocatalytic performance due to their unique electronic, optical and catalytic properties. The localized plasmon resonance (LSPR) effect allows metal particles to absorb part of the visible light and generate high-energy hot electrons. These hot electrons are captured by the metal sites loaded on the semiconductor, driving surface chemical reactions and forming high concentrations of CO on the catalyst surface to improve C2+ product selectivity.
[0004] In order to achieve photocatalytic reduction of CO2 to C 2+ In order to achieve high catalytic performance of the product, the designed catalyst needs to have the following capabilities at the same time: 1. High photogenerated carrier transfer ability and utilization rate, 2. Highly efficient adsorption of *CO intermediates and low activation energy of carbon-carbon coupling reactions.
[0005] CN116651459A discloses a tandem photocatalyst of indium oxide loaded with copper single atoms and its preparation and application. The preparation method comprises the following steps: (1) weighing In(NO3)3 and terephthalic acid, dissolving them in DMF, heating and stirring, centrifuging, washing and drying to obtain a precursor In-MOF; (2) dispersing the precursor In-MOF in an ethanol solution, adding a CuCl2 solution and stirring for ion exchange to obtain a precursor InCu-MOF; (3) calcining the precursor InCu-MOF to obtain a tandem photocatalyst of indium oxide loaded with copper single atoms with a loose porous microtubule morphology, which is the target product. The catalyst Cu exists in the form of a single atom, coordinates with oxygen in In2O3, forms a stable low-valence state and low-coordination mode, has a wide light absorption range, greatly improves its ability to reduce carbon dioxide (CO2) under visible light, and exhibits excellent selectivity for reducing CO2 to ethanol, and simultaneously oxidizes water to oxygen in a gas-liquid reaction system. However, as a rare metal on earth, indium is expensive and difficult to popularize industrially.
[0006] CN118142587A discloses a copper-based MOF photocatalyst, a preparation method and an application thereof, the synthesis of a constructed copper-based MOF compound and its use in the photocatalytic direct conversion of carbon dioxide into a multi-carbon product acetone. The technical field relates to the preparation and application of a copper-based MOF composite material for directly converting carbon dioxide into a high-value C3 product acetone under visible light irradiation at room temperature and having a special three-atom site NH2-Cu-NH2, but the selectivity for ethanol is not high. Summary of the invention
[0007] The present invention is directed to photocatalytic carbon dioxide preparation of C 2+ The products such as ethanol and acetaldehyde are not efficient, especially the selectivity of ethanol is not high. A method for preparing a single-atom alloy photocatalyst is provided. The synergistic effect between Cu and Au overcomes the CC coupling that is difficult to occur during the reaction process, thereby realizing the efficient and high-selective conversion of CO2 into ethanol.
[0008] To achieve the above object, the technical solution adopted by the present invention is: A method for preparing a single-atom alloy photocatalyst comprises the following steps: Step 1, preparing a carbon material carrier CN by grinding and roasting, dispersing the carbon material carrier CN in a solution containing a Cu element, and removing the solution by rotary evaporation to obtain a Cu-loaded carrier Cu@CN; Step 2, reducing Cu@CN with hydrogen to obtain a Cu nanoparticle-loaded carrier, dispersing the carrier in a gold precursor solution, mixing, removing the solvent by rotary evaporation, washing and drying the obtained solid to obtain the single-atom alloy photocatalyst.
[0009] The present invention dopes metal Au atoms onto Cu nanoparticles on the surface of a carrier by combining wet mixing with atomic replacement reduction, and the catalyst surface presents Cu nanoparticles of small size, relatively uniform particle size and uniform distribution. The Au-Cu single-atom metal active center on the surface of the photocatalyst is constructed to adjust the charge on the Au surface to increase its *CO adsorption capacity, thereby achieving a high concentration of *CO on the catalyst surface during the reaction, reducing the reaction energy barrier of carbon-carbon coupling, and thus achieving a highly selective CO2 reduction reaction to produce ethanol.
[0010] The mass content of Cu in the single-atom alloy photocatalyst is 0.1-20 wt %; preferably, the mass content of Cu is 0.1-10 wt %; further preferably, the mass content of Cu is 1-10 wt %; excessive Cu loading is prone to agglomeration of copper atoms, which in turn reduces the catalytic efficiency.
[0011] The mass content of Au in the single-atom alloy photocatalyst is 0.001-10 wt %, preferably 0.001-5 wt %, and more preferably 0.1-5 wt %.
[0012] The mass ratio of Cu to Au in the single-atom alloy photocatalyst is 100: 1 to 3: 1. Preferably, the mass ratio of Cu to Au is 50: 1 to 5: 1, more preferably the mass ratio of Cu to Au is 20: 1 to 5: 1, and most preferably the mass ratio of Cu to Au is 15: 1 to 10: 1. Under this ratio, the synergistic effect of gold and copper in the catalyst is the strongest, and the catalyst is more selective for the photocatalytic reaction of carbon dioxide with ethanol.
[0013] The temperature of hydrogen reduction in step 2 is 200-300° C. More preferably, the temperature of hydrogen reduction is 250-300° C., and more preferably, the temperature of hydrogen reduction is 250-280° C.
[0014] More preferably, the hydrogen reduction conditions are: 250°C for 2 h; the heating rate is set to 2-8°C / min; the H2 flow rate is set to 100 mL / min; and the H2 purity is 99.999%.
[0015] The carbon material carrier includes any one or more of graphite sheets, graphene, and carbon nanotubes; The carbon material carrier includes any one or more of graphite sheets, graphene, and carbon nanotubes doped with metal or non-metal elements.
[0016] The grinding includes any one of ball milling, grinding and stamping; the particle size of the carbon nanocarrier CN is 100-1000nm.
[0017] The grinding is ball milling, firstly ball milling and then calcining, and then ball milling and then calcining for a second time; The ball milling speed is 100-870 rpm / min, and the ball milling time is 4-5 h; the primary calcination temperature is 200-300° C., and the calcination time is 2-6 h; the secondary calcination temperature is 500-600° C., and the calcination time is 4-6 h.
[0018] The particle size of the carbon carrier is reduced by grinding and calcining, the surface area is increased, and the impurities in the carrier are fully pyrolyzed and removed. The temperature is carried out under the condition of ensuring the stability of the carrier. If the calcination temperature is too low, the impurities cannot be completely removed, and if it is too high, the carrier structure may be destroyed.
[0019] The solution containing the Cu element includes a copper precursor solution and / or a solution of copper nanoparticles; The copper precursor includes any one or more of copper nitrate, oxalate, and halide salt; The gold precursor includes any one or more of gold nitrate, gold oxalate, and gold halide salt.
[0020] The present invention also provides a single-atom alloy photocatalyst prepared by the preparation method, wherein the size of the single-atom alloy photocatalyst is 5-40 nanometers, wherein the mass content of Cu is 0.1 wt%-20 wt%; the mass content of Au is 0.001-10wt%.
[0021] Preferably, the single-atom alloy photocatalyst has a low content of precious metal Au, only 0.001-10 wt%, preferably 0.5 wt%; at the same time, after fixed-bed H2 reduction, the Cu nanoparticles are evenly dispersed in the carrier and have a small size, and the catalyst Cu nanosize is 2-10 nanometers.
[0022] The present invention also provides the use of the single-atom alloy photocatalyst in the photocatalytic carbon dioxide reduction reaction. The high synergy between the noble metals Au and Cu in the catalyst makes it catalyze carbon dioxide reduction with excellent effect, and can achieve high selectivity to obtain ethanol products under the condition of pure water as solvent.
[0023] The photocatalytic reaction temperature is 25-250°C, and the reaction pressure is 0.1-4.0 Mpa.
[0024] Preferably, the light source for the photocatalytic reaction is: 50-300 W xenon lamp (PLS-SXE300 + / UV xenon lamp light source); the purity of carbon dioxide is: 90-99%.
[0025] In the prior art, a certain amount of N,N-dimethylformamide (DMF), sodium sulfite (Na2SO3), etc., needs to be added to the reaction solvent as a reaction promoter or sacrificial agent to promote the efficiency of the photocatalytic reaction and achieve high selectivity of carbon dioxide to ethanol. The photocatalyst described in the present invention can achieve high selectivity of carbon dioxide to ethanol under pure water conditions. In terms of application, the use of cheap and abundant H2O as an electron donor should be the direction and goal of photocatalytic CO2 reduction.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, a simple atom replacement synthesis strategy is used to prepare a photocatalyst with a single-atom alloy. By doping Au atoms on the surface of Cu nanoparticles supported on a carrier, the synergistic effect between metals in the catalyst is further enhanced. The catalyst catalyzes CO2 reduction under light conditions and achieves excellent ethanol selectivity.
[0027] (2) The catalyst of the present invention can be used for the carbon dioxide reduction reaction by directly using pure water as an electron donor, thereby achieving a high ethanol conversion rate.
[0028] (3) The loading amount of precious metal Au in the catalyst of the present invention is lower than that of conventional catalysts, and the reduction in raw material cost is conducive to the industrial promotion of the catalyst. In addition, the preparation process of the catalyst is simple and the raw materials are simple and easy to obtain, so it has the potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the CN carrier prepared in Example 1.
[0030] Figure 2 Preparation of Cu5Au for Example 1 0.5 @ TEM image of CN catalyst.
[0031] Figure 3 The carrier CN, the precursor Cu5@CN and the catalyst Cu5Au prepared in Example 1 0.5 @XRD pattern of CN.
[0032] Figure 4 This is a comparison chart of the catalytic performance of catalysts with different gold doping amounts prepared in Example 1.
[0033] Figure 5 This is a comparison chart of the catalytic performance of catalysts prepared at different reduction temperatures in Example 1 and Example 2.
[0034] Figure 6 This is a comparison chart of the catalytic performance of catalysts prepared by different reduction methods in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0036] The raw materials used in the following specific embodiments are all purchased from the market. The metal Cu precursor used in Example 3 is CuC2O4, with a molecular weight of 151.56; the metal Cu precursors used in other embodiments and comparative examples are all Cu(NO3)2·3H2O, with a molecular weight of 409.81; the metal Au precursor is HAuCl4·4H2O, with a molecular weight of 411.85.
[0037] Example 1 Preparation of Cu5Au with different Au contents using hydrogen reduction method x @CNSample (1) 2.0 g of nanographite powder was placed in a 50 mL ball mill, and zirconium oxide balls were added according to the ball-to-material ratio. After being placed in an argon (Ar) atmosphere for 12 h, the ball mill was continued to be filled with argon after being ball milled at 870 rpm / min for 1 h. (2) After taking out the above raw materials, ball mill them at 100-870 rpm / min for 5 h. The obtained solid was calcined at 250°C in a muffle furnace for 4 h. After cooling to room temperature, it was calcined again at 550°C for 3 h to remove impurities. (3) The raw materials were transferred to argon and allowed to stand for 12 h, followed by ball milling at 870 rpm / min for 5 h to obtain a two-dimensional carbon nanosheet carrier, denoted as CN.
[0038] (4) Take 200 mg of CN carrier and transfer it to copper nitrate solution containing 5 wt% Cu. After stirring for 1 h, let it stand overnight. The resulting solution was rotary evaporated at 40 °C to obtain a two-dimensional carbon carrier loaded with Cu precursor, which was recorded as Cu5@CN.
[0039] (5) Take 85 mg of the above Cu5@CN solid and reduce it with hydrogen at 250 °C in a fixed bed for 2 h. After cooling to room temperature, the obtained solid is immediately transferred to chloroauric acid solutions of different mass concentrations (containing Au mass fractions of 0.1 wt%, 0.5 wt%, 1.0 wt%, 2.0 wt%, and 3.0 wt%, respectively), stirred for 4 h, and then allowed to stand overnight.
[0040] (6) The above solution was rotary evaporated at 40 °C. The obtained solid was washed twice with deionized water by centrifugation and then dried at 40 °C in vacuum. The obtained solid was the catalyst with 5 wt% Cu loaded and different Au loadings, denoted as Cu5Au X @CN, where x is the loading amount of Au, specifically marked as Cu5Au 0.1 @CN、Cu5Au 0.5 @CN, Cu5Au1@CN, Cu5Au2@CN, Cu5Au3@CN.
[0041] Figure 1 This is the SEM image of the prepared two-dimensional carbon nanosheet carrier. From the image, we can see that CN is stacked in a sheet-like manner.
[0042] Figure 2 Cu5Au 0.5 TEM image of @CN catalyst. Figure 2 It can be seen that the Cu nanoparticles are evenly distributed on the CN support with a size of 2-40 nm.
[0043] Figure 3Cu5@CN, a precursor of Cu loaded on a two-dimensional carbon carrier, and the prepared Cu5Au 0.5 X-ray diffraction spectrum of @CN catalyst. Figure 3 It can be seen that no obvious change in the crystal structure was found after Cu and Au were loaded on CN.
[0044] Example 2 Cu5Au prepared by hydrogen reduction method under three different temperature conditions 0.5 @CNSample (1) Place 2.0 g of nanographite powder into a 50 mL ball mill, add zirconium oxide balls according to the ball-to-material ratio, and place in an argon (Ar) atmosphere for 12 h; (2) ball milling the above raw materials at 870 rpm / min for 1 h and then continue to fill with argon gas; (3) After taking out the above raw materials, ball mill them at 870 rpm / min for 5 h. The obtained solid was calcined at 250°C in a muffle furnace for 4 h. After cooling to room temperature, it was calcined again at 550°C for 3 h. (4) The raw materials were transferred to argon and placed under fine conditions for 12 h, followed by ball milling at 870 rpm / min for 5 h to obtain a carbon support material, which was also denoted as CN.
[0045] (5) Take 200 mg of the C carrier and transfer it to a copper nitrate solution containing 5 wt% Cu. After stirring for 1 h, let it stand overnight. The resulting solution was rotary evaporated at 40 °C to obtain a C-loaded Cu precursor, which was recorded as Cu5@C.
[0046] (6) Take 85 mg of the above solid and reduce it with hydrogen at different temperatures in a fixed bed for 2 h. After cooling to room temperature, the obtained solid is immediately transferred to a 0.5 wt% chloroauric acid solution, stirred for 4 h and allowed to stand overnight.
[0047] (7) The above solution was evaporated at 40 °C. The obtained solid was washed twice with deionized water by centrifugation and then dried at 40 °C in vacuum. The obtained solid was the catalyst with 5 wt% Cu and 0.5 wt% Au loading, denoted as Cu5Au 0.5 @CN-x, where x is the hydrogen reduction temperature, specifically Cu5Au 0.5 @CN-200,Cu5Au 0.5 @CN-300.
[0048] Comparative Example 1 Cu5Au prepared by different chemical reduction methods 0.5 @CNSample (1) Place 2.0 g of nanographite powder into a 50 mL ball mill, add zirconium oxide balls according to the ball-to-material ratio, and place in an argon (Ar) atmosphere for 12 h; (2) ball milling the above raw materials at 870 rpm / min for 1 h and then continue to fill with argon gas; (3) After taking out the above raw materials, ball mill them at 870 rpm / min for 5 h. The obtained solid was calcined at 250°C in a muffle furnace for 4 h. After cooling to room temperature, it was calcined again at 550°C for 3 h. (4) The raw materials were transferred to argon and placed under fine conditions for 12 h, followed by ball milling at 870 rpm / min for 5 h to obtain a carbon support material, which was denoted as CN.
[0049] (5) Take 200 mg of CN carrier and transfer it to copper nitrate solution containing 5 wt% Cu. After stirring for 1 h, let it stand overnight. The resulting solution was rotary evaporated at 40 °C to obtain C-loaded Cu precursor, which was recorded as Cu5@C.
[0050] (6) Take 85 mg of the above solid and put it into a solution. Use 800 mg of sodium borohydride, ascorbic acid and hydrazine hydrate as reducing agent to reduce it. After the reduction is completed, immediately transfer the obtained solid to 0.5 wt% chloroauric acid solution at room temperature, stir for 4 h and then let it stand overnight.
[0051] (7) The above solution was evaporated at 40 °C. The obtained solid was washed twice with deionized water by centrifugation and then dried at 40 °C in vacuum. The obtained solid was the catalyst with 5 wt% Cu and 0.5 wt% Au loaded on CN, denoted as Cu5Au. 0.5 @CN(z), wherein z is the catalyst reduced by different reducing agents, specifically z is A (ascorbic acid), B (sodium borohydride), and C (hydrazine hydrate).
[0052] Catalyst performance evaluation The performance of the catalysts prepared in the examples and comparative examples for photocatalytic carbon dioxide reduction was tested and evaluated as follows: Figure 4-6 As shown, the catalytic reaction is carried out in a photocatalytic reactor, and photocatalysis is achieved by simulating solar radiation through a xenon lamp.
[0053] Application Example 1 1. Weigh 20 mg of the catalysts of Examples 1-2 and Comparative Example 1 and a magnetic stirrer and place them at the bottom of a quartz reactor with an inner diameter of 50 mm.
[0054] 2. Pour 5 mL of ultrapure water into a quartz cup and place it on a magnetic stirrer and stir at 870 rpm / min for 10 min to fully disperse the catalyst.
[0055] 3. Place the quartz cup in the photocatalytic reactor, introduce high-purity CO2 to 2.0 MPa, then release the gas. Repeat the operation three times to fully exhaust the residual air in the reactor.
[0056] 4. Introduce high-purity gas to 4.0 MPa, set the reaction temperature and stirring speed, and turn on the xenon lamp.
[0057] 5. After the reaction is completed, the gas after the reaction is introduced into GC to analyze the gas phase product; the liquid after the reaction is centrifuged and the supernatant is taken to detect the liquid phase product by H-NMR.
[0058] The data of the photocatalytic preparation of ethanol in the examples and comparative examples are summarized in Table 1. The test results of the photocatalytic reduction of carbon dioxide by the catalysts with different gold doping amounts in Example 1 are shown in Table 1. Figure 4 It shows that under light conditions, the catalyst Cu5@CN does not produce ethanol without Au doping; as the amount of Au atoms doped on the surface of the Cu nanoparticles on the carrier continues to increase, the selectivity and activity of ethanol in the product show a trend of first increasing and then decreasing. When the Au doping amount is 0.5 wt%, the catalyst has the highest ethanol activity and selectivity.
[0059] Table 1 Catalytic performance data of catalysts prepared in Examples and Comparative Examples
[0060] like Figure 5 As shown in Example 2, the catalytic effects of the catalysts under different hydrogen reduction conditions at different temperatures are compared. When the hydrogen reduction temperature is 250°C, Cu5Au 0.5 @CN sample has the best activity. It is worth noting that after hydrogen reduction at 300℃, Cu5Au 0.5 @CN-300 activity is only slightly improved, but considering economic and operational issues, 250°C is used as the most preferred condition in the present invention.
[0061] like Figure 6 As shown, by comparing different reduction methods, it was found that Cu5Au0.5@CN showed the best ethanol activity and selectivity when reduced by hydrogen compared with the chemical reduction methods using ascorbic acid, sodium borohydride and hydrazine hydrate.
Claims
1. A method for preparing a single-atom alloy photocatalyst, characterized in that: Includes steps: Step 1, preparing a carbon material carrier CN by grinding and roasting, dispersing the carbon material carrier CN in a solution containing a Cu element, and removing the solution by rotary evaporation to obtain a Cu-loaded carrier Cu@CN; Step 2, reducing Cu@CN with hydrogen to obtain a Cu nanoparticle-loaded carrier, dispersing the carrier in a gold precursor solution, mixing, removing the solvent by rotary evaporation, washing and drying the obtained solid to obtain the single-atom alloy photocatalyst.
2. The method for preparing the single-atom alloy photocatalyst according to claim 1, characterized in that: The mass content of Cu in the single-atom alloy photocatalyst is 0.1-20 wt%; The mass content of Au in the single-atom alloy photocatalyst is 0.001-10 wt %.
3. The method for preparing the single-atom alloy photocatalyst according to claim 1, characterized in that: The mass ratio of Cu to Au in the single-atom alloy photocatalyst is 100:1 to 3:
1.
4. The method for preparing a single-atom alloy photocatalyst according to claim 1, characterized in that: The temperature of hydrogen reduction in step 2 is 200-300°C.
5. The method for preparing a single-atom alloy photocatalyst according to claim 1, characterized in that: The carbon material carrier includes any one or more of graphite sheets, graphene, and carbon nanotubes; Or, the carbon material carrier includes any one or more of graphite sheets, graphene, and carbon nanotubes doped with metal or non-metal elements; The grinding includes any one of ball milling, grinding and punching; the size of the carbon nanocarrier CN is 100-1000 nm.
6. The method for preparing a single-atom alloy photocatalyst according to claim 1, characterized in that: The grinding is ball milling, firstly ball milling and then calcining, and then ball milling and then calcining for a second time; The ball milling speed is 100-870 rpm / min, and the ball milling time is 4-5 h; the primary calcination temperature is 200-300° C., and the calcination time is 2-6 h; the secondary calcination temperature is 500-600° C., and the calcination time is 4-6 h.
7. The method for preparing a single-atom alloy photocatalyst according to claim 1, characterized in that: The solution containing the Cu element includes a copper precursor solution and / or a solution of copper nanoparticles; The copper precursor includes any one or more of copper nitrate, oxalate, and halide salt; The gold precursor includes any one or more of gold nitrate, gold oxalate, and gold halide salt.
8. The single-atom alloy photocatalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The size of the single-atom alloy photocatalyst is 5-40 nanometers, wherein the mass content of Cu is 0.1-20 wt%; and the mass content of Au is 0.001-10 wt%.
9. Use of the single-atom alloy photocatalyst according to claim 8 in a photocatalytic carbon dioxide reduction reaction.
10. The use according to claim 9, characterized in that: The photocatalytic reaction temperature is 25-250°C, and the reaction pressure is 0.1-4.0 Mpa.
Citation Information
Patent Citations
Method for non-invasive efficient purification of single-wall carbon nano tube
CN102139872A
Transition metal monatomic active catalyst as well as preparation method and application thereof
CN113600170A
Copper monatomic material, preparation method thereof and application of copper monatomic material in photocatalytic CO2 reduction
CN113856730A
Light-stable ultrathin BiOCl atomic layer anchored transition metal monatomic catalyst as well as preparation and application of light-stable ultrathin BiOCl atomic layer anchored transition metal monatomic catalyst
CN114797911A
Nitrogen-defect-containing porous carbon nitride supported monatomic copper catalyst and preparation method and light nitrogen fixation application thereof
CN115069290A
Cited By
Preparation method and application of monatomic Ni modified AuNi alloy catalyst
CN120662330A
An atomically dispersed copper-silver bimetallic photocatalyst, and a preparation method and application thereof
CN122538213A